Қорақалпоғистонда узлуксиз таълим тизимида ҳуқуқий таълим самарадорлигини оширишда педагогик фикрларнинг ривожланиши (SCIENCE and SOCIETY, 2016)
The article deals with the problems, connected with the study of influence of pedagogical ideas on increasing the effectiveness of teaching juridical sciences. The main issues in the spheres of education and science have also been investigated. The author presents valuable points of view and opinions of the prominent scientists about the future of Pedagogics. The materials of the article can be used bay the specialists in Pedagogics.